Quantitative detection of iodine in the stratosphere - Koenig, Theodore K. (2020)
Oceanic emissions of iodine destroy ozone, modify oxidative capacity, and can form new particles in the troposphere. However, the impact of iodine in the stratosphere is highly uncertain due to the lack of previous quantitative measurements. Here, we report quantitative measurements of iodine monoxide radicals and particulate iodine (Iy,part) from aircraft in the stratosphere. These measurements support that 0.77 ± 0.10 parts per trillion by volume (pptv) total inorganic iodine (Iy) is injected to the stratosphere. These high Iy amounts are indicative of active iodine recycling on ice in the upper troposphere (UT), support the upper end of recent Iy estimates (0 to 0.8 pptv) by the World Meteorological Organization, and are incompatible with zero stratospheric iodine injection. Gasphase iodine (Iy,gas) in the UT (0.67 ± 0.09 pptv) converts to Iy,part sharply near the tropopause. In the stratosphere, IO radicals remain detectable (0.06 ± 0.03 pptv), indicating persistent Iy,part recycling back to Iy,gas as a result of active multiphase chemistry. At the observed levels, iodine is responsible for 32% of the halogen-induced ozone loss (bromine 40%, chlorine 28%), due primarily to previously unconsidered heterogeneous chemistry. Anthropogenic (pollution) ozone has increased iodine emissions since preindustrial times (ca. factor of 3 since 1950) and could be partly responsible for the continued decrease of ozone in the lower stratosphere. Increasing iodine emissions have implications for ozone radiative forcing and possibly new particle formation near the tropopause.